Analisis Kepatuhan Melaksanakan Hemodialisa Pada Penderita Gagal Ginjal Di Rsi Siti Khadijah Palembang Tahun 2016 - Noviana; Chairil Zaman; Rismala Kesuma (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat (IAKMI) Provinsi Sumatera Selatan, 2018)
According to WHO that  prevalency acute and chronic kidney failure reached 50 %, which is known only get 25 % treatment and 12,5 % who got treatment well. In Siti Khadijah hospital Palembang has an percentage increasment of chronic renal failure patiens in hemodialysis installation has 10 % that is in 2013 patients with kidney failure  about 1,262 patients with hemodialysis action 10.387. In 2014, about 1.331 patients with 10.392 hemodialysis actions. In 2015 about 1.381 patiens with 10.868. acts of hemodialysis. In 2016 about 1430 patients with kidney failure with 10.963 hemodialysis action. The purpose of the study to determine the picture of compliance  of patients with renal failure who do hemodialysis at Siti Khadijah Hospital Palembang in 2016.. This research design is based on analytical survey with cross sectional approach using secondary data. With a population of 116 respondents. Total sample amounted to 116 respondents. The results of the study was 116 respondents, 107 people of old aged (92,2,%), 66 people of male (56,9%), 82 people of low education 70,7%), 93 people of knowledge (80%), 98 people of hoigh motivation (84,5%), 62 people of easy to reach acces service (53,4%), 96 patients with attitude response (82,8 %), 84 people with family support (75 %), 107 role nurse (92,25). 92 compliance people. In Bivariate analysis of the research variables were unrelated to the level of adherence in implementing hemodialysis placement in Siti Khadijah Islamic Hospital good, compliance patient to hemodialysis implement is good and improve of quality service with periodically training.